Who Speaks Words without Knowledge? A Response to Wilcox and Bimson - Brinks, C. L. (Journal for the study of the Old Testament, 2010)
This article joins in a discussion between Karl G. Wilson and John J. Bimson regarding the interpretation of Job 38.2. Wilson argued that the question “Who is this…?” refers to Elihu rather than Job, indicating that Elihu’s speeches are original rather than additions to the book. Bimson refuted Wilcox’s interpretation by appealing to the content of the divine speeches and Job’s near quotation of 38.2 in 42.3. This article demonstrates the weaknesses in Bimson’s refutation by comparing the grammatical construction of the question in 38.2 to similar constructions elsewhere in the Old Testament and noting its context in the book of Job as a whole. This article concludes that Bimson’s refutation was unsuccessful, and that Wilcox’s argument merits further response.